Taken from a cafe in Paris, France. You can see the Eiffel Tower from almost anywhere in Paris. It was a dream of mine to sip coffee at an outdoor cafe with the Eiffel Tower in the background and that's exactly what we did, Europe - Pena, Kaury Leona
International Experience, 2013